2014
DOI: 10.4236/jwarp.2014.619161
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Protection Zones for the Main Discharge Area of the Gran Sasso Aquifer (Central Italy) through an Integrated Geomorphological and Chronological Approach

Abstract: The paper proposes a study for the delineation of protection zones in the main discharge area of the Gran Sasso aquifer (Central Italy). At this aim, starting from a detailed geological and hydrogeological reconstruction, the study was divided into the following phases: 1) development of a conceptual model of water flow in the study area; 2) creation of a 3D numerical model in order to simulate the groundwater flow in saturated conditions, both at the basin and at fine-scale; 3) flow path analysis through dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Locally, the geological and hydrogeological framework is quite complex because of the heterogeneity of the deposits; Figure 2 shows the detailed hydrogeological set-up of the study area, from the literature data and available borehole stratigraphies [37][38][39][40]. The Gran Sasso carbonate complex is in contact with the marly-clayey one, creating a no-flux hydrogeological limit.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Locally, the geological and hydrogeological framework is quite complex because of the heterogeneity of the deposits; Figure 2 shows the detailed hydrogeological set-up of the study area, from the literature data and available borehole stratigraphies [37][38][39][40]. The Gran Sasso carbonate complex is in contact with the marly-clayey one, creating a no-flux hydrogeological limit.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Locally the geological and hydrogeological framework is quite complex because of heterogeneity of the deposits; from literature data and available boreholes' stratigraphies [15][16][17][18], in Fig. 2 the detailed hydrogeological set-up of the study area is shown: the Gran Sasso carbonate complex is in contact with the marly -clayey one creating a no-ux hydrogeological limit.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Kazemi (1969) proposed a method to estimate the main hydrogeological parameters of dual permeability aquifers, whereas for anisotropic aquifers the most commonly used methods have been developed by Papadopulos (1969), Fig. 5 -Example of hydrogeological map, in which the type of permeability (and then the type of aquifer) and the main groundwater flow direction is defined (Biava et al 2014).…”
Section: Hydraulic Conductivity From In Situ Testsmentioning
confidence: 99%
“…Fig. 5 -Esempio di carta idrogeologica, nella quale vengono definiti i tipi di permeabilità (e di conseguenza la tipologia di acquifero), nonché le direzioni di flusso principali (Biava et al 2014). Hantush (1966) and Neuman et al (1984).…”
Section: Hydraulic Conductivity From In Situ Testsunclassified